1999
DOI: 10.1039/a903461g
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced charge separation of methylphenothiazine in microporous titanosilicate M-ETS-10 (M=Na++K+, H+, Li+, Na+, K+, Ni2+, Cu2+, Co2+) and Na+, K+-ETS-4 molecular sieves at room temperature

Abstract: The photoionization of methylphenothiazine in microporous titanosilicates M-ETS-10 (M \ Na`] K`, H`, Li`, Na`, K`, Ni`, Cu2`and Co2`) and Na,K-ETS-4 molecular sieves with UV irradiation at room temperature is studied. Methylphenothiazine cation radicals are produced in M-ETS-10 molecular (PC`) sieves and are characterized by electron paramagnetic resonance (EPR) and di †use reÑectance (DR) UV-vis spectroscopy. Microporous titanosilicate Na,K-ETS-10 and its ion-exchanged molecular sieves with alkali and transit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 25 publications
0
32
0
Order By: Relevance
“…It has been demonstrated that application of post-synthetic treatment to titanosilicates can change the state of titanium atoms from Ti(IV) to catalytically active Ti(III) [50]. Such a reduction to paramagnetic Ti in ETS-10 titanosilicates can occur as a result of high-temperature treatment under vacuum [51], treatment with H 2 or CO at moderate to high temperatures [52], ion exchange [5354], UV [55] or γ-irradiation [51]. To characterize the state of Ti in the titanosilicates participating in catalytic tests and the possible presence of impurities, the EPR spectra of these samples were measured at 70 K (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It has been demonstrated that application of post-synthetic treatment to titanosilicates can change the state of titanium atoms from Ti(IV) to catalytically active Ti(III) [50]. Such a reduction to paramagnetic Ti in ETS-10 titanosilicates can occur as a result of high-temperature treatment under vacuum [51], treatment with H 2 or CO at moderate to high temperatures [52], ion exchange [5354], UV [55] or γ-irradiation [51]. To characterize the state of Ti in the titanosilicates participating in catalytic tests and the possible presence of impurities, the EPR spectra of these samples were measured at 70 K (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, the stability of PyC n þ increases from PyC 1 to PyC 16 due to an increased inductive effect in PyC n þ as a function of longer alkyl chain lengths. 39,41,42 A semiquantitative measure of the efficiency of the photoreaction is obtained from the amount of alkylpyrene cation radicals produced relative to the number of alkylpyrene molecules present prior to photoirradiation. The estimated photoconversion is $15%, which is relatively high.…”
Section: Resultsmentioning
confidence: 99%
“…The photoionization of methylphenothiazine in microporous titanosilicates M-ETS-10 (M = N+ + K+, H+, Li+, Na+, K+, Ni+, Cu2+ and Co2+) and Na,K-ETS- 4 with UV irradiation at room temperature has been studied [123]. Methylphenothiazine cation radicals are produced in M-ETS-10 materials but none are detected by EPR or diffuse reflectance UV-Vis spectroscopy on Na,K-ETS-4.…”
Section: Optical Propertiesmentioning
confidence: 99%